Buddleoside-rich Chrysanthemum indicum L. extract modulates macrophage-mediated inflammation to prevent metabolic syndrome induced by unhealthy diet - Yiqing Zhou; Jie Su; Yingjie Dong; Ziwen He; Yajun Wang; Suhong Chen; Guiyuan Lv (BMC, 2024)
Abstract Background Metabolic syndrome (MetS) is a precursor to the development of many diseases (atherosclerosis, diabetes, etc.). It is marked by disruptions in glucose and lipid metabolism, along with hypertension. Numerous types of risk factors contribute to the development of the MetS, inflammation and insulin resistance are present throughout the metabolic abnormalities. Chrysanthemum indicum L. is a traditional Chinese plant used for both tea and medicine, known for its high content of total flavonoids, which are important secondary metabolites. Our research led to the extraction of a Buddleoside-Rich Chrysanthemum indicum L. extract (BUDE) which has demonstrated anti-inflammatory properties. Nonetheless, the specific role and mechanism of BUDE in preventing MetS remain unclear. Methods The study initially evaluated the role of BUDE in preventing MetS. Subsequently, it investigated the anti-inflammatory properties of BUDE in the liver and pancreas in response to unhealthy diets. It then examined the level of insulin resistance and pancreatic β-cell function induced by inflammation. Additionally, an lipopolysaccharide (LPS)-induced macrophage inflammation model was used to further investigate the ameliorative effects of BUDE in inflammation. Results BUDE has hypotensive, hypoglycemic and hypolipidemic effects. It can also resolve the imbalance between macrophage subpopulations, impede the triggering of the NF-κB signaling pathway, reduce the secretion of inflammatory mediators, ameliorate insulin resistance, and safeguard organs such as the liver and pancreas from inflammatory damage. These effects collectively contribute to preventing the development of MetS. Discussion BUDE has the ability to modulate macrophage-mediated inflammation, leading to improved insulin resistance. Additionally, it delivers antihypertensive, hypoglycemic, and hypolipidemic effects, offering a potential for preventing MetS.